Analisis Pengaruh Car, Npl, Nim, Bopo Dan Ldr Terhadap Roe Pada Bank Umum Swasta Nasional Devisa Di Indonesia - Monica Monica (Universitas Tarumanagara, 2019)
This research is meant to find out the influence of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Biaya Operasional/Pendapatan Operasional (BOPO), and Loan to Deposit Ratio (LDR) to the Return on Equity (ROE) at Private Foreign Exchange National Bank in Indonesia. The population is all Private Foreign Exchange National Bank in Indonesia. This study has been done by using purposive sampling method with two criteria so 20 companies have been selected as samples. The analysis technique has been done by using multiple linear regressions. The results showed that CAR, NIM, and LDR did not effect to ROE, whereas NPL and BOPO has negative effect to ROE. Where it was proved that together CAR, NPL, NIM, BOPO, and LDR have influence to ROE. Management should improve the company’s financial performance, especially on the non performing loan and operational efficiency of the business so that the company can improve to ROE